P17 Evaluation of new orleans criteria for cranial CT scan in mild traumatic brain injury at an emergency trauma unit of a developing country. Issue 3 (14th February 2019) - Yusuf, AS; Mahmud, MR; Dalhat, NK; Olayiwola, AI; Alfin, JD; Abimbola, AI
Abstract : Objectives: To assess compliance to New Orleans Criteria for cranial CT scan and its predictive value for intracranial pathology in mild TBI. Design: A retrospective review. Subjects: All patients with mild traumatic brain injury presenting at the emergency unit of a National Trauma Centre of a Developing Country over 24 months. Methods: Patients information were retrieved from medical record and entered into SPSS spreadsheet. The New Orleans Criteria (NOC) was used to determine indications for brain CT scan. Compliance to the criteria was determined. The CT scan findings were evaluated in all patients that had scan and the findings were compared between those met NOC and those who did not. Results: One-hundred and eighteen patients were studied. Majority were males 92 (82%) with mean age of 27 year. Most injuries (66.9%) resulted from road traffic crashes. Among 65 (55.1%) patients who met NOC only 41 (63.1%) had CT scan while 25 (47.2%) patients who did not had CT giving a compliance rate of 58.5%. Twenty three (56.1%) patients who met NOC had abnormal CT compared to 9 (36%) patients that did not. The most common abnormal CT findings in both groups were skull vault fractures (9 for NOC group and 2 for non NOC group) only two patients had surgical intervention and both met NOC criteria. Conclusions: The compliance for NOC guideline was below average in our Centre. NOC guideline is useful in predicting abnormal CT findings. There is a need for continuous education of emergency physicians to ensure optimal CT scan utilisation in mild TBI.